The Essential Talmud - Steinsaltz, Adin (New York Basic Books, Inc., Publishers, 1976)
An Israeli rabbi and scholar conveys the spirit of the Talmud as he treats its composition, traditions, structure, and laws.
Translated from the Hebrew by Chaya Galai
Keywords: Talmud -- Introductions. Judaism. Talmud - Introductions. 11.21 Jewish religious literature. Talmud